The Legacy of the Baby Boomers or the French Social System? Issues of Equality and Brain Drain - Patron, Marie-Claire.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This book aims to identify key factors influencing the increasing brain drain of French early and mid-career graduates primarily to Anglo-Saxon countries in order to avoid the inexorable outcome of their tertiary studies: precarious employment conditions relegating them to the status of intellectual underclass in France. This qualitative ethnographic study investigated the experiences of 38 French nationals and expatriates aged between 21 and 48 to provide a voice to the increasing number of students and graduates who despair at the thought of witnessing their years of study culminate in a perennial cycle of training, unemployment, internship. What distinguishes the French from their European counterparts who also struggle to secure employment and a decent future? These unprecedented circumstances in Europe are as a result of the global financial crisis and the current sovereign debt predicament. Who is responsible for the quandary in which French graduates find themselves in the stratified French society of today, where globalisation has made academic mobility de rigueur? France risks losing her talented Generation X to more accepting countries where a spirit of meritocracy exists and economic rewards are awarded after years of tertiary education and assiduousness. A large number of constituents belonging to Baby Boomer Generation are ensconced in comfortable government positions or are established in lucrative careers reserved for the upper echelons of the privileged classes. Are the Baby Boomers to blame for the predicament of Generation X, for failing to transmit intergenerational equality to subsequent generations? Will the new government deliver on the promises to grant France$1 (Bs youth the economic rewards they deserve, and the respect and equality that the previous generation have taken for granted?s
Keywords: Education; Education; Education (general).